New approaches in ceramic repair systems: Review - Gülfem Ergün (Cumhuriyet University, 2016)
Veneering porcelain fracture is a complication which is seen in all dental ceramic systemscontaining all ceramic and metal-ceramic restorations. Repairing the fractured veneeringporcelain is important for the maintenance of restoration. The repair process is important interms of maintinance of the restoration and can be performed intra-orally or extra-orally. Untila more durable ceramic systems have been developed, direct repair techniques are a practicalsolution for both the patient and the clinician. Nowadays, the focused topics to provide adhesionfor ceramic repair is to creat mechanical and chemical connection. In order to ensure satisfactoryadhesion between the repair material and the fractured surface, certain surface treatmentsshould be applied. The composition differences of exposed surfaces in the fracture area alsocause differences in surface treatment to be applied. In this review, studies involving currentceramic repair methods, surface treatments and the differences between the materials have beendiscussed. Online search of the dental literature in Pubmed and Cochrane Library from 2000 to2015 is performed with ceramic, fracture, repair, bonding, hydrofluoric acid, air abrasion, laser,silica coating, composite, silane and different combinations of these keywords. After reading thesummaries of the screening of publications, 100 researches have been considered appropriate toreview within the subject area. It is observed that the type of the material which is exposed onthe fracture surface play an important role and to choose the ideal surface treatment method tobe used in the repair process is an important factor directly on the success of the fracture repair.